433 Palynostratigraphy of the eocene esmeraldas formation, middle Magdalena Valley Basin, Colombia (2012)
The Eocene EsmeraldasFormation isa very importantoil reservoir intheMiddle Magdalena ValleyBasin, Colombia, which is a preduct of the fragmentatienof a Cenozoic forelandbasinby the uplift of the Northem Andes. Ihe lateralcentinuity of the formation,as well as its correlations with lithostratigraphic units inadjacent basins isnot clearly understood. The Los CorrosFossilHorizon,a molluscan horizonin the upper partof the Esmeraldas Formation,has been used to tracethe top of the formation, Thishorizonisnot laterallycontinuous over thebasinand its age is still debatable. Some of the key palynostratigraphic events inNorthernSouth America are net present inthepalynological record of the Esmeraldas, Palynologicaldata from 82 samples from an eutcrop section intheNuevo Mundo Synclinearea and from seven previouslystudied wells have been integratedwith a palynologicalzonation of nonhem South America inorder to datctheEsrneraldasForrnation.The age ranges from the lateEarly Eocene to the Late Eocene. The Esmeraldas Forrnationiscorrelative withthe upper Picacho ForTnation and the lowerpartof the ConcentracionForrnationin the EasternCoTdillera, and theupper Mirador Forrnationand thebaseof theCarboneraFormationintheLlanosFeothills. [[heLos Corros FossilHorizon is Late Eocene and is time-correlative with a marine transgression inthe central Llanos Foothills,A non-menic multidimensional scaling analysis suggests that florasfrom the Middle Magdalena Valleywere differentfromthe Llanos Foothillsarea during the Middle to Late Eocene. This is apparently due to taphonomic effects. The results efthis study conuibute to a betterunderstanding of theoverall evolution ef the Middle Magdalena ValleyBasin and the evolution of thenonhem Andes.